Ferroptosis regulator FANCD2 is associated with immune infiltration and predicts worse prognosis in lung adenocarcinoma - Ye, Chenyang; Lu, Yier; Yuan, Zhijun; Mi, Mi; Qi, Lina; Yuan, Ying; Weng, Shanshan (Frontiers in Genetics, 2022)
Lung adenocarcinoma (LUAD) remains one of the leading causes of cancer-related death. Although immunotherapy has been shown to improve survival in LUAD patients, only a select group of LUAD patients could benefit from it. The correlation between ferroptosis and the tumor immune environment requires further investigation in the setting of LUAD. An analysis using The Cancer Genome Atlas (TCGA)-LUAD cohort systematically evaluated the expression levels of ferroptosis regulators between LUAD and normal tissues and demonstrated the correlation of ferroptosis regulators with the immune checkpoint B7-H3 expression. Based on consensus clustering analysis, we divided LUAD patients into two subtypes according to the expression pattern of ferroptosis regulators. Cluster 2 patients showed more favorable overall survival (OS) (p < 0.001) and disease-free survival (DFS) (p < 0.001) than Cluster 1 patients. CIBERSORT analysis indicated that Cluster 1 patients harbored higher infiltrated levels of uncharacterized cells, CD4+ T cells (nonregulatory), and myeloid dendritic cells, while Cluster 2 patients were more correlated with B cells, M1 macrophages, natural killer cells (NK cells) and regulatory T cells (Tregs). More importantly, we identified FANCD2 as a potentially unfavorable prognostic factor that was overexpressed in LUAD and positively associated with the checkpoint molecule B7-H3 expression. In addition, higher FANCD2 expression was related to a higher tumor immune dysfunction and exclusion (TIDE) score, indicating lower responder rates to cancer immunotherapeutics. In summary, our study suggested a relationship between immune infiltration and ferroptosis and that FANCD2 is a potential biomarker for clinical outcomes and a therapeutic target for LUAD therapy concerning ferroptotic regulation. Our findings may help to advance personalized treatment and improve the prognosis of LUAD.